Sharing Information and Threshold Ambiguity in Public Bads Prevention - Islam Md Tawhidul; Kenta Tanaka; Koji Kotani (World)
Public bads prevention problems, such as climate change, require people to cooperate above a certain threshold, which is ambiguous and varies in many situations. In that case, people conjecture and share some information about the threshold. However, little is known about how sharing such information affects people to cooperate. We experimentally examine how people’s cooperative choices are influenced by ambiguity and sharing information about the conjectures in public bads prevention, hypothesizing that sharing the information does not necessarily contribute to cooperation. We conduct the laboratory experiments with 400 subjects under five treatments, each of which differs in ambiguity as well as in presence or absence of sharing the information. We find that (i) the percentages of cooperative choices are nonmonotonic, decreasing and then increasing over ambiguity levels and (ii) sharing the information tends to uniformly discourage cooperation, and the negative impact becomes prominent as the ambiguity levels rise. The result demonstrates an adverse effect between sharing information and threshold ambiguity on cooperation, being in sharp contrast with the literature. Overall, this study suggests that how or what information is shared among people should be carefully reconsidered for resolving any public bads problem involving threshold ambiguity, as everybody is able to easily publicize their conjectures during an era of digital democracy. Additionally, providing unified public information or fostering agreement could help improve cooperation and enhance collective efforts in public bads prevention.